2019
DOI: 10.2147/copd.s213519
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation Of <em>HHIP</em> Polymorphisms And Their Relationship With Chronic Obstructive Pulmonary Disease Phenotypes</p>

Abstract: PurposeWe aimed to correlate three polymorphisms of the Hedgehog Interacting Protein (HHIP) gene with the three main phenotypes of the chronic obstructive pulmonary disease (frequent exacerbator (FE), asthma/COPD overlap (ACO), and emphysema with hyperinflation).Patients and methodsA cross-sectional study was carried out in the Department of Pulmonology at the Rio de Janeiro State University from February 2015 to July 2018. A total of 81 patients diagnosed with COPD according to the criteria of the Global Init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Gli2 may be found in basal AEC nuclei, but can also be observed subciliary in ciliated cells, suggesting the presence of autocrine and paracrine signalling in the epithelium. We then focused on Hhip, another Shh receptor acting as an inhibitor of HH signalling, which is particularly interesting, as genetic alteration of Hhip was associated with COPD and emphysema in genome-wide associated studies and murine models [4,5,[31][32][33][34][35]. We detected Hhip in differentiated cells, but the absence of differential Hhip localization between non-COPD and COPD samples suggested that genetic alterations of Hhip may impact protein function rather than protein expression.…”
Section: Discussionmentioning
confidence: 98%
“…Gli2 may be found in basal AEC nuclei, but can also be observed subciliary in ciliated cells, suggesting the presence of autocrine and paracrine signalling in the epithelium. We then focused on Hhip, another Shh receptor acting as an inhibitor of HH signalling, which is particularly interesting, as genetic alteration of Hhip was associated with COPD and emphysema in genome-wide associated studies and murine models [4,5,[31][32][33][34][35]. We detected Hhip in differentiated cells, but the absence of differential Hhip localization between non-COPD and COPD samples suggested that genetic alterations of Hhip may impact protein function rather than protein expression.…”
Section: Discussionmentioning
confidence: 98%
“…Mice with haploinsufficiency (HHIP +/-) are more susceptible to developing severe emphysema due to exposure to cigarette smoke than wild type mice (HHIP +/-) (5) . In this study, it was found that the presence of polymorphisms in the HHIP gene at positions rs13118928, rs1828591 and rs10519717 did not make Javanese smokers susceptible to COPD (16) . (8,9,17) and in Mongolians (10) .…”
Section: Discussionmentioning
confidence: 68%
“…For rs1828591, one of the most highly associated polymorphisms in other populations (Lamontagne et al, 2013;Kerkhof et al, 2014;Bártholo et al, 2019), the case-control analysis showed that AA COPD patients have higher protein levels than control subjects. Serum protein levels analyzed in the dominant model confirmed an association with the AA genotype in the COPD-TS group (AA vs. AG + GG).…”
Section: Discussionmentioning
confidence: 99%